Pelatihan Tari Kreasi dan Pementasan Hasil Karya Tari Di Sekolah Dasar Negeri Sikumana 2 Kupang - Manubey, Johana; Kambuno, Cynthia T; Metan, Yosefina; Dadik, Melvi Agustina (Devotion: Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to provide training in creative dance and facilitate the performance of dance works at SD Negeri Sikumana 2 Kupang. The focus is on creative dance training and performance, involving 30 students as training participants and 200 students as performance participants. The activity successfully enhanced students' understanding of the development of creative dance in NTT. During the training, students were guided by dance mentors to learn proper dancing techniques and practice new creative dances. The training results were then presented in an art performance held at the end of the activity. The program received a positive response from the school and is expected to be conducted regularly to support arts activities in schools. Keywords: creative dance; performance; elementary school students